Analisis Landasan Filosofis, Historis, dan Yuridis Pendidikan Agama Islam dalam Sistem Pendidikan Nasional - Siti Mabruroh (Moral : Jurnal kajian Pendidikan Islam, 2026)
Islamic Religious Education plays an important role in developing students' character, morality, and religious values amid the various challenges of modern life. The advancement of globalization, technological development, and shifts in educational paradigms require Islamic Religious Education to continuously adapt while maintaining the fundamental values of Islamic teachings. This study aims to analyze the philosophical, historical, and juridical foundations of Islamic Religious Education as well as its position within the Indonesian national education system. This study employed a library research method with a qualitative approach through the analysis of various literature sources, including scientific articles, and relevant laws and regulations. The findings reveal that Islamic Religious Education is supported by strong philosophical, historical, and juridical foundations that complement one another in its implementation. Furthermore, the values of Islamic Religious Education are relevant to the Outcome-Based Education (OBE) paradigm, which emphasizes holistic learning outcomes, and are supported by the Internal Quality Assurance System (SPMI) in ensuring educational quality.